Treatment options for autoimmune bullous dermatoses other than systemic steroids: A systematic review and network meta‐analysis. Issue 6 (7th July 2020) - Salman, Samar; Awad, Mina; Sarsik, Sameh; Ibrahim, Ahmed M.; Fathi, Mohamed; Agha, Nadim Y.; Anis, Ruba; El Ashal, Gehad; Salem, Mohamed L.
Abstract: Autoimmune blistering diseases can eventually cause life‐threatening complications if left untreated. Although there is no cure for these bullous diseases; their therapy is based on suppressing the immune system to cease the de novo formation of the generated antibodies. The current study aimed to assess the safety and efficacy of using standing alone alternative therapies beyond systemic steroids for management of autoimmune bullous diseases. We searched six literature databases for both randomized and quasi‐randomized clinical trials that assessed the efficacy of drugs other than systemic steroids in autoimmune bullous diseases. Outcomes were calculated as odds ratios with 95% confidence‐interval. We used the R software to perform conventional and network meta‐analyses with a frequentist approach. The network ranking order for 629 bullous pemphigoid patients, from the best to the worst was, clobetasol propionate cream (40 mg; ( P ‐score = .87), clobetasol propionate cream (10‐30 mg; P ‐score = .77), nicotinamide plus tetracycline ( P ‐score = .56), steroids ( P ‐score = .29) and doxycycline ( P ‐score = .01). Limitations of this study are the small sample of the included studies except for blister trial and lack of randomization in most trials. To conclude, Combined doxycycline and nicotinamides are safer and more effective option for extensive bullous pemphigoid patients than the usual use of systemic steroids. For limited disease, topical corticosteroid (40 mg/d) use provides a safer and better response modality than the other proposed treatments.